REPRODUCTIVE FUNCTION DISORDERS IN WOMEN OF REPRODUCTIVE AGE AFTER A NEW CORONAVIRUS INFECTION - Ковалева, Екатерина Владимировна; Баринов, Сергей Владимирович (Mother and Baby in Kuzbass, 2024)
Since the start of the COVID-19 pandemic, many cases of reproductive dysfunction have been reported after a new coronavirus infection in women of reproductive age. Research and literature analysis confirm that COVID-19 can affect the female reproductive system. This may manifest itself in changes in the menstrual cycle, amenorrhea and other aspects. Additional research is required to fully understand the mechanisms of impact of COVID-19 on the female reproductive system. It is important to develop appropriate treatment and prevention strategies to help women regain reproductive health after illness. Research into the impact of COVID-19 on the female reproductive system remains a pressing issue and represents an important area of medical research.The aim of the research – to conduct an analytical review of modern sources of scientific literature on the issues of reproductive dysfunction in women of reproductive age after suffering a new coronavirus infection.Materials and methods. An analysis of foreign and domestic sources on this topic was carried out.Results. Based on the latest scientific data, the presented review describes the key factors in the pathogenesis of reproductive disorders, and studies the frequency of occurrence of this pathology. The main methods of therapy are considered, on the basis of which we can conclude that at this stage there is no effective method for treating reproductive dysfunction in women of reproductive age after suffering a new coronavirus infection.Conclusion. Our analysis indicates that reproductive dysfunction in women after a new coronavirus infection is an urgent problem and requires further study.
Keywords: reproductive dysfunction; new coronavirus infection; women of reproductive age